2017
DOI: 10.1007/s00270-017-1821-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a New X-Ray Imaging System for Interventional Procedures: Improved Image Quality and Reduced Radiation Dose

Abstract: PurposeTo compare image quality and radiation exposure between a new angiographic imaging system and the preceding generation system during uterine artery embolization (UAE).Materials and MethodsIn this retrospective, IRB-approved two-arm study, 54 patients with symptomatic uterine fibroids were treated with UAE on two different angiographic imaging systems. The new system includes optimized acquisition parameters and real-time image processing algorithms. Air kerma (AK), dose area product (DAP) and acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
3
11
3
Order By: Relevance
“…This technique was reported to facilitate a significant radiation dose reduction of both digital fluoroscopy (DF) and digital subtraction angiography (DSA) for various image-guided procedures in the field of interventional radiology Abbreviations: AK, Air kerma; BMI, Body Mass Index; DAP, Dose area product; DEB-TACE, Drug-eluting Bead chemoembolization; DF, Digital fluoroscopy; DSA, Digital subtraction angiography; DSA-DAP, Digital subtraction angiography dose area product; HU, Heat Units; PACS, Picture Archiving and Communication System; RAK, Reference air kerma; RDSR, Radiation Dose Structured Reports; SID, Source-to-Image Receptor Distance; TACE, Transarterial chemoembolization. [13][14][15] and interventional cardiology [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This technique was reported to facilitate a significant radiation dose reduction of both digital fluoroscopy (DF) and digital subtraction angiography (DSA) for various image-guided procedures in the field of interventional radiology Abbreviations: AK, Air kerma; BMI, Body Mass Index; DAP, Dose area product; DEB-TACE, Drug-eluting Bead chemoembolization; DF, Digital fluoroscopy; DSA, Digital subtraction angiography; DSA-DAP, Digital subtraction angiography dose area product; HU, Heat Units; PACS, Picture Archiving and Communication System; RAK, Reference air kerma; RDSR, Radiation Dose Structured Reports; SID, Source-to-Image Receptor Distance; TACE, Transarterial chemoembolization. [13][14][15] and interventional cardiology [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the radiation or ICM dose normally results in reduced image quality. Noise reduction algorithms are reported to provide a possible solution in this regard [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Mondshine et al also found that the technology was associated with a decreased cumulative dose (0.78 Gy) and skin DAPs (146.35 Gy cm 2 ) on their flat–panel angiography system (Axiom Artis, Siemens Medical Systems, Germany). Recent literature by Schernthaner et al , published in 2018 supports previous findings that the flat–panel angiography units produce significantly improved image quality and reduced radiation exposure. These benefits further justify the clinical viability of UAE as a non‐invasive procedure and offset any potential, but rare, risks that may be involved with this technique …”
Section: Discussionmentioning
confidence: 58%